ANALISIS KESUBURAN PERAIRAN BERDASARKAN KELIMPAHAN FITOPLANKTON DI MUARA SUNGAI PORONG, SIDOARJO - Devi Setyowardani; Nor Sa’adah; Nirmalasari Idha Wijaya (Universitas Hang Tuah, 2021)
The disposal of Lapindo mud which carries nutrients and other dissolved organic matter can cause mass enrichment and death of organisms due to the reduced amount of light entering the waters. The existence of phytoplankton can provide information about the state of the waters. This study aims to determine the fertility of the waters of the Porong River through the abundance of phytoplankton. This research was conducted from October to January 2021. Sampling was carried out at three stations. The plankton sampling method was carried out horizontally and identified using the Sedgwick Rafter Counting Cell (SRCC). Nitrate and phosphate water samples used for analysis were measured by Uv-Vis Spectrophotometry. Data analysis includes phytoplankton density, diversity index, uniformity index, and dominance index. The results showed that the composition of the phytoplankton species found during the observation was dominated by diatom classes (13 genera ) and dinoflagellates (2 genera). The abundance value of phytoplankton is 122.293 – 867.776 cells/m3. The water fertility status in the Porong River Sidoarjo is in the eutrophic category, namely waters with high fertility levels.